Novel Targets for Stroke Therapy: Special Focus on TRPC Channels and TRPC6 - Liu, Lu; Gu, Lijuan; Chen, Manli; Zheng, Yueying; Xiong, Xiaoxing; Zhu, Shengmei (Frontiers in Aging Neuroscience, 2020)
Stroke remains a leading cause of death, disability, and medical care burden worldwide. However, transformation from laboratory findings toward effective pharmacological interventions for clinical stroke has been unsatisfactory. Novel evidence has been gained on the underlying mechanisms and therapeutic potential related to the transient receptor potential(TRP) channels in several disorders. The TRP superfamily consists of a diverse group of Ca2+ permeable nonselective cation channels. In particular, the members of TRP subfamilies, TRP canonical channels(TRPCs) and TRPC6, have been found in different cell types in the whole body and have high levels of expression in the central nervous system(CNS). Notably, the TRPCs and TRPC6 channel have been implicated in neurite outgrowth and neuronal survival during normal development and in a range of CNS pathological conditions. Recent studies have shown that suppression of TRPC6 channel degradation prevents ischemic neuronal cell death in experimental stroke. Accumulating evidence supports the important functions of TRPC6 in brain ischemia. We have highlighted some crucial advancement that points toward an important involvement of TRPCs and TRPC6 in ischemic stroke. This review will make an overview of the TRP and TRPC channels due to their roles as targets for clinical trials and CNS disorders. Besides, the primary goal is to discuss and update the critical role of TRPC6 channels in stroke and provide a promising target for stroke prevention and therapy.